New Zealand indigenous Myrtaceae in foreign botanic gardens: testing the sentinel plant concept for biosecurity risk assessment - Boyd-Wilson, Kirsty S.H.; Marroni, M. Virginia; McNeill, Mark R.; Teulon, David A.J. (New Zealand Plant Protection, 2021)
The use of sentinel or expatriate plants is a growing concept for risk assessment in plant biosecurity. This approach involves ascertaining the presence and impact of pests and pathogens on plants foreign to a given location but planted in international botanic gardens or arboreta. The data obtained provide information on the potential pest status of these pests and pathogens, as invasive alien species (IAS), to plant species in their native or indigenous range. Assessment of the biosecurity threat from IAS for indigenous plants not found within the geographic distribution of these pests and pathogens is challenging, however, as they may be relatively taxonomically distinct from plants found in the distribution of the IAS and can be in different climates and environments. We examine the sentinel/expatriate concept in relation to risk assessment for myrtle rust (Austropuccinia psidii) on New Zealand Myrtaceae on these plants found in botanic gardens and arboreta outside New Zealand. Between September 2017 and September 2018, we identified and then contacted 65 botanic gardens or arboreta that putatively had New Zealand Myrtaceae and were within the known distribution of myrtle rust. We asked for information on the presence of New Zealand Myrtaceae species in their collections and whether these plants were infected by myrtle rust. Sixteen gardens/arboreta responded; most were in Australia or the United States. Only one of these gardens provided information that was useful for biosecurity risk assessment for myrtle rust on New Zealand Myrtaceae. The results are discussed in the context of plant biosecurity risk assessment and the broader sentinel/expatriate plant concept.